Angularly Stable, Transparent and Flexible Modified Octagonal Shaped Frequency Selective Surface (FSS) for Sub-GHz 5G Applications - Kumar, Gotte Ranjith; S, Swetha; S, Deepan; S, Loganathan; A, Muthu Manickam; S, Lavanya (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2025)
This paper offers a newly size-reduced Frequency Selective Surface (FSS) featuring band-stop behavior at 4.2 GHz. This developed FSS includes a mushroom-shaped arm with an octagonal patch. The patch is extensively adjusted by incorporating further mushroom-shaped arms, leading to a lower resonance and wider bandwidth. The designed FSS is made up of just a 11 × 11 mm unit cell on a flexible acrylic substrate that is 1 mm thick. The proposed FSS had a 1 GHz bandwidth with a centre resonance frequency of 4.2 GHz. Due to the distinct polarization behavior of this FSS, the Transverse Magnetic (TM) and Transverse Electric (TE) modes are unique and have a steady angular property up to 45º. Measurements of S-parameters for TE and TM polarizations have been validated experimentally over the 2–8 GHz frequency spectrum for both normal and oblique incident angles up to 45°. Excellent agreement between the measured and simulated data is demonstrated, verifying the FSS performance with a frequency variation of less than 3% and preserving constant band-stop properties across all measured orientations. It may be appropriate for incorporation into applicable clothes in a variety of areas because of its simplicity and ease of fabrication.